The 5-modular characters of the sporadic simple fischer groups fi22 and fi23 - Hiss, Gerhard; Lux, Klaus; Breuer, Thomas (Communications in algebra, 1994)
The 5-modular decomposition numbers of the two simple Fischer groups Fi22and Fi23 and also those of the two maximal subgroups2. Fi22 and of Fi23 are determined. In an appendix Thomas Breuer comments on his construction of the ordinary character tables of the groups , which occur as maximal subgroups of 2. Fi22respectively Fi23- The results were obtained with the help of the computer algebra systems MOC [4] and GAP [10].